2014
DOI: 10.1007/s11368-014-1012-3
|View full text |Cite
|
Sign up to set email alerts
|

Net and gross N transformation rates in subtropical forest soils under aerobic and anaerobic conditions

Abstract: Purpose This study investigated the differences between net and gross rates of N transformation in subtropical forest soils under aerobic and anaerobic conditions. We aim to explore the factors responsible for the differences observed and to evaluate the ability of net and gross N transformation measurements to reflect the occurrence and stimulation of N transformation in subtropical forest soils. Materials and methods Subtropical soil samples from adjacent native forest (NF) and two plantation forest sites (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…In addition, sediment C:N ratio negatively covaried with both GNM and GAI rates in the ECS (Table ), indicating that TOC available contents and C:N stoichiometry might play an important role in sediment N mineralization and N immobilization in this ecosystem. A similar relationship between GNM rate and C:N ratio has been reported in other ecosystems [ Zhu et al , ; Regehr et al , ; Zhao et al , ]. Hence, the spatial patterns of N mineralization and immobilization in the study area were remarkably affected by the bioavailability of TOC and TN.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, sediment C:N ratio negatively covaried with both GNM and GAI rates in the ECS (Table ), indicating that TOC available contents and C:N stoichiometry might play an important role in sediment N mineralization and N immobilization in this ecosystem. A similar relationship between GNM rate and C:N ratio has been reported in other ecosystems [ Zhu et al , ; Regehr et al , ; Zhao et al , ]. Hence, the spatial patterns of N mineralization and immobilization in the study area were remarkably affected by the bioavailability of TOC and TN.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, microbes preferentially assimilate NH 4 + due to higher energy costs associated with biological NO 3 − assimilation, and thus, the presence of NH 4 + may greatly inhibit microbial NO 3 − immobilization [ Zhu et al , ]. Meanwhile, NO 3 − immobilization plays a negligible role in total microbial N immobilization under anaerobic conditions [ Zhao et al , ]. Moreover, numerous studies have demonstrated that microbial NH 4 + immobilization is the dominant process of NH 4 + consumption [ Di et al , ; Bengtsson et al , ; Bedard‐Haughn et al , ; Gütlein et al , ], which can effectively remove the accumulated NH 4 + in sediments and maintain ecological health [ Matheson et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, together with the results of previous studies, our data indicate that the possible influence of climate gradients might be masked by the large spatial heterogeneity in gross N turnover in forest ecosystems (Burton, Chen, Xu, & Ghadiri, 2007). With regard to the magnitudes of GA and GN, Zhao, Cai, and Xu (2015) reported rates of GA and GN of 5.00 mg kg −1 day −1 and up to 2.19 mg kg −1 day −1 , respectively, for subtropical forests in China. A further study by Zeng et al (2014) has found comparably high rates, that is, GN rates of 4, 5.3 and 6 mg kg −1 day −1 in coniferous, deciduous and evergreen broad- ranging from 2.5 to 8.6 mg kg −1 day −1 , and GN rates in the range of 0.6-3.49 mg kg −1 day −1 .…”
Section: Spatial Pattern and Environmental Controls Of Soil Gross Nsupporting
confidence: 81%
“…Thus, together with the results of previous studies, our data indicate that the possible influence of climate gradients might be masked by the large spatial heterogeneity in gross N turnover in forest ecosystems (Burton, Chen, Xu, & Ghadiri, ). With regard to the magnitudes of GA and GN, Zhao, Cai, and Xu () reported rates of GA and GN of 5.00 mg kg −1 day −1 and up to 2.19 mg kg −1 day −1 , respectively, for subtropical forests in China. A further study by Zeng et al.…”
Section: Discussionmentioning
confidence: 99%